2008
DOI: 10.1302/0301-620x.90b4.20522
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in total hip replacement

Abstract: A prospective, multi-centre study was carried out on 1421 total hip replacements between January 1999 and July 2007 to examine if obesity has an effect on clinical outcomes. The patients were categorised into three groups: non-obese (body mass index (BMI) < 30 kg/m(2)), obese (BMI 30 to 40 kg/m(2)) and morbidly obese (BMI > 40 kg/m(2)). The primary outcome measure was the change in Oxford hip score at five years. Secondary outcome measures included dislocation and revision rates, increased haemorrhage, deep in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
138
4
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(157 citation statements)
references
References 35 publications
10
138
4
5
Order By: Relevance
“…Given the association between BMI and development of hip osteoarthritis [1], THAs will be performed on an increasing number of patients with obesity. Of particular concern is the risk of dislocation in patients with obesity when using a posterior approach and when the BMI is greater than 35 kg/m 2 [2,6,14,18,28,35,36]. The specific frequency and the best approaches for preventing this serious complication are unclear [4,21,32,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the association between BMI and development of hip osteoarthritis [1], THAs will be performed on an increasing number of patients with obesity. Of particular concern is the risk of dislocation in patients with obesity when using a posterior approach and when the BMI is greater than 35 kg/m 2 [2,6,14,18,28,35,36]. The specific frequency and the best approaches for preventing this serious complication are unclear [4,21,32,39].…”
Section: Discussionmentioning
confidence: 99%
“…When obesity is defined as a body mass index (BMI) greater than 30 kg/m 2 in adults, obesity is recognized as an independent risk factor for postoperative hip dislocation in several studies [2,6,8,15,18,22,28,35]. However, in these patients with obesity, it is not known whether the risk is only in the early postoperative period or if the risk persists several years after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have attempted to clarify the interaction between obesity and dislocation following THA [14][15][16]. Azodi et al demonstrated that a high body mass index (BMI) increased the risk of dislocation after THA [16].…”
Section: Introductionmentioning
confidence: 99%
“…Azodi et al demonstrated that a high body mass index (BMI) increased the risk of dislocation after THA [16]. In particular, morbidly obese patients (BMI >40) had a statistically significant higher risk of dislocation [3,15]. By contrast, other studies did not find evidence of an increased rate of dislocation caused by obesity after THA [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, associated high rates of pain, as well as joint destruction and postural changes in those who are excessively obese can be expected to impact the pathogenesis of hip joint osteoarthritis both before and after surgery more profoundly than non-obese situations [18,19]. Alternately, the constellation of obesity, immobility and pain can independently raise the risk for hip joint osteoarthritis, and its disability [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%